The atomic force microscope as a mechano–electrochemical pen - Obermair, Christian; Wagner, Andreas; Schimmel, Thomas (Beilstein Journal of Nanotechnology, 2011)
We demonstrate a method that allows the controlled writing of metallic patterns on the nanometer scale using the tip of an atomic force microscope (AFM) as a “mechano–electrochemical pen”. In contrast to previous experiments, no voltage is applied between the AFM tip and the sample surface. Instead, a passivated sample surface is activated locally due to lateral forces between the AFM tip and the sample surface. In this way, the area of tip–sample interaction is narrowly limited by the mechanical contact between tip and sample, and well-defined metallic patterns can be written reproducibly. Nanoscale structures and lines of copper were deposited, and the line widths ranged between 5 nm and 80 nm, depending on the deposition parameters. A procedure for the sequential writing of metallic nanostructures is introduced, based on the understanding of the passivation process. The mechanism of this mechano–electrochemical writing technique is investigated, and the processes of site-selective surface depassivation, deposition, dissolution and repassivation of electrochemically deposited nanoscale metallic islands are studied in detail.
Keywords: atomic force microscopy; deposition; electrochemistry; nanoelectronics; nanofabrication; nanolithography; nanotechnology; NEMS and MEMS; scanning probe lithography